Aktivitas Pelarutan Fosfat Isolat Azospirillum spp. asal Lahan Pasir Besi - Sodik Wuryanto; Oedjijono Oedjijono; Sarjiya Antonius (Biology Department, Faculty of Science and Technology, Univeristas Jambi, Indonesia, 2015)
Iron sand lands have a low organic matter content as it contains of Iron (Fe) found nearly all over the coastal or beach in Indonesia. Phosphorous is one of macronutrient with considered role for plant promotion. One group of bacteria that are in an environment of rooting plants on land sand iron was Azospirillum spp. The purpose of this study was is to know the phosphate solubilizing activities of Azospirillum spp. isolates from land sand iron. The results showed that some isolates of Azospirillum spp. origin of iron sand land capable of solubilizing phosphate in qualitative and quantitative.